Evaluating the effectiveness of local wisdom-based disaster mitigation education in primary schools - Lestari, Wiwik; Dwiningrum, Siti Irene Astuti; Sujarwo, Sujarwo; Azhari, Ichwan; Damanik, Ibnu Hajar (Edelweiss Applied Science and Technology, 2025)
This study aims to evaluate the effectiveness of a disaster mitigation education program based on local wisdom in enhancing disaster preparedness among primary school students. A quasi-experimental design with a non-equivalent control group was employed, involving 346 students from Medan and Yogyakarta. The experimental group received an intervention incorporating local cultural values and practices into disaster education, while the control group followed the standard curriculum. Data were collected using pre-tests and post-tests and analyzed using paired and independent t-tests. The findings indicate a statistically significant improvement in the experimental group’s understanding of disaster mitigation, with a post-test average score of 78.4 compared to 52.3 in the control group (p < 0.001). The results highlight the effectiveness of integrating local wisdom into disaster education to enhance students' contextual understanding and readiness. In conclusion, the local wisdom-based model presents a promising and culturally relevant approach to disaster education. Practical implications suggest that policymakers and educators should adopt this model to foster disaster-resilient behaviors from an early age, particularly in regions prone to climate-induced hazards.